PERANCANGAN SISTEM INFORMASI RAWAT JALAN DI PUSKESMAS GUNA MENUNJANG PELAPORAN LB4 DENGAN METODE OBJECT ORIENTED - Mauli Nurnajjah; Azmallisani; Leni Herfiyanti; Riky Faza (POLITEKNIK PIKSI GANESHA, 2021)
Research aimed to design of visit outpatient to support reporting LB4 information system by using Object Oriented Method.The research method used is qualitative method with descriptive approach. Data collection techniques used are interview techniques, observation, and literature study. The method of development system is the waterfall method. Problems found by the writer’s during the research that is officer have difficulty in the form of recording reports that much be done not optimal and officers to fill out the report at the time of patient registration so that the occurrence of patient accumulation and late submission of reports. The suggestions given is the need for a system of visits outpatient to support reporting LB4 and MySQL as the database and is expected to solve existing problems. Keywords: Design, Information System, Outpatient, LB4 Reporting.